Advancing Disaster Risk Financing and Insurance in ASEAN Member States : Framework and Options for Implementation, Volume 2. Technical Appendices - World Bank (Washington, DC, 2013)
This report is part of a project being jointly conducted by the World Bank, the Global Facility for Disaster Reduction and Recovery (GFDRR), the Association of Southeast Asian Nations (ASEAN) Secretariat, and United Nations International Strategy for Disaster Reduction (UNISDR). It aims to provide capacity building on disaster risk financing and insurance (DRFI) in ASEAN Member States. DRFI is a relatively new topic and, therefore, training and capacity building of local stakeholders is essential. Governments must understand the benefits and the limitations of disaster risk financing and insurance as part of their comprehensive Disaster Risk Management (DRM) strategies. This report presents main findings and recommendations on DRFI in the ASEAN region. Following the World Bank disaster risk financing and insurance framework, it consists of five chapters, including this introduction. Chapter two presents a preliminary economic and fiscal risk assessment of natural disasters in ASEAN Member States. Chapter three provides an overview of the fiscal management of natural disasters currently implemented by ASEAN Member States. Chapter four reviews the state of the private catastrophe insurance markets, including property catastrophe risk insurance, agricultural insurance, and disaster micro-insurance. Chapter five identifies five main recommendations for strengthening the long-term financial and fiscal resilience of ASEAN Member States against natural disasters, as part of their broader disaster risk management and climate change adaptation agendas.